Toxicidade e efeitos subletais de toxinas Cry de Bacillus thuringiensis Berliner em diferentes populações de Plutella xylostella (L.) (Lepidoptera: Plutellidae) em laboratório - De Bortoli, Caroline Placidi [UNESP] (2014)
Plutella xylostella (Linnaeus , 1758) (Lepidoptera: Plutellidae), diamonback moth, is a major insect pest of crucifers (Brassicaceae) in Brazil and worldwide. Although it can be controlled with synthetic insecticides such as biological products, populations of P. xylostella can be quickly selected for resistance to several chemical or biological insecticides. In addition, different populations of P. xylostella may arise due to geographic isolation, resulting in reproductive isolation and physiologically distinct populations with different sensitivities to various control tactics. This variation requires management systems tailored to particular populations. The most common insecticides used to control P. xylostella based on entomopathogenic bacterium Bacillus thuringiensis (Bacillaceae) (Bt). Although many studies focus on the action way of Bt to several agricultural pests such as P. xylostella, for example, many doubts still persist particularly regarding their sublethal effects, mechanism of action and toxicity of Bt proteins. The objective of this research was to analyze the virulence and sublethal effects of Cry proteins, as well investigate factors affecting the susceptibility of Diamondback to Bt (protein level, the midgut bacteria and mutations in the ABCC2 gene) in five Brazilian populations and one population from England. Susceptibility bioassays with 5 Brazilian populations (PC, PA, PX, SBT and Bt) and one from England (UK) of P. xylostella and Cry1Ac, Cry2Aa, and Cry1IE Bt toxins were performed by estimating its virulence and sublethal effects. How Cry2Aa Cry1IE toxins did not cause larvae mortality for all populations, tests were performed just with Cry1Ac. Enzymatic and molecular experiments with the larvae guts were also performed to investigate the factors that affecting the susceptibility of insects to toxins produced by Bt. In those bioassays were analyzed total protein, the ...